Exploratory Study on Internalization of Character Values through Educational Profession Course - Mesterjon Mesterjon; Suwarni Suwarni; Diah Selviani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study was based on the findings during teaching and learning process at FKIP Universitas Dehasen Bengkulu (the Faculty of Educational Science and Teacher Training of Dehasen University of Bengkulu). There was a phenomenon of declining of good character value and morality. This is because of the misused of advancing technology by students that brings negative impact on the students' character and morality. This phenomenon was especially found among new students of FKIP (Faculty of Educational Science and Teacher Training) on their early stage of study. At the meeting of Educational Profession (Profesi Pendidikan) course, we did early observation by making contract with the new student.. They generally still brought their local character and moralor their old behavior. This could be seen, for example, they talked to their lecturers and seniors impolitely or often used their local language.  Everyone's patience was needed in dealing withthis phenomenon. As the lectures progressed, especially Educational Profession course, we tried to internalize character values toward the students. This had positive impact for them. Today, they are found to be more polite, for example, they greet their lecturers and seniors when they meet them. This study dealt with character values such as: religious, discipline, honest, hard work, responsible, love peace, appreciate achievements, and friendly or communicative. This Exploratory study which was done to internalize character value of the students, has positive impact, this can be seen fromthepositive progress of students' character. Students who already have good character will keep learning to have better personality. This wil affect their future job, especially if they become teachers.